2015
DOI: 10.1108/jaee-05-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structures influence on audit fee

Abstract: Purpose -The purpose of this paper is to investigate the association between corporate ownership structures and audit fees paid to external auditors by Malaysian companies listed on Bursa Malaysia. This study focusses on the extent of the auditor's reliance on the client's internal control inasmuch as the corporate ownership structures are varied, and, ultimately, affect the audit fees. Design/methodology/approach -This study applies the agency theory in formulating three hypotheses that guide the results anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
9
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(90 citation statements)
references
References 67 publications
(80 reference statements)
10
62
9
9
Order By: Relevance
“…This result is consistent with earlier finding who studied the association of FOOWN and quality of financial reporting and discovered a negative association between FOOWN and quality of financial reporting in Spain [41]. The result is not consistent with the previous studies by that FOOWN has a positive association with the quality of financial reporting [90,91].…”
Section: Logistic Regression Analysissupporting
confidence: 75%
See 1 more Smart Citation
“…This result is consistent with earlier finding who studied the association of FOOWN and quality of financial reporting and discovered a negative association between FOOWN and quality of financial reporting in Spain [41]. The result is not consistent with the previous studies by that FOOWN has a positive association with the quality of financial reporting [90,91].…”
Section: Logistic Regression Analysissupporting
confidence: 75%
“…They establish a significant and positive association between audit fees and firms with larger FOOWN. Nelson and Mohamed-Rusdi found a positive and significant relationship between audit quality and that of corporates with both foreign and INOWN [91]. Contrary to these findings, de Albornoz Noguer and Rusanescu, who assessed the FOOWN and quality of financial reporting, found a negative relationship between FOOWN and quality of financial reporting in Spain [41].…”
Section: Foreign Ownershipmentioning
confidence: 98%
“…Abdul Wahab et al (2009) find a positive relationship between institutional ownership and audit fees and they too found that the audit fees are higher for PCON firms during the pre-2007 period. In addition, a study by Sherliza and Nur Farha (2015) show a significant positive relationship between audit fees and firms with larger foreign ownership and government ownership but no significant relationship with firms with higher managerial ownership. Amir (2014) found that family ownership firms pay fewer fees for the audit work.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 93%
“…They proposed that a high level of managerial ownership helps in reducing the conflict between managers and shareholder, which is expected to lead to peter performance. Similarly, other researchers (Li et al, 2007;Nelson & Mohamed-Rusdi, 2015) argued that managerial ownership reduces conflict of interests and therefore enhances the efficiency of management shareholders in doing their job effectively which will improve the performance of the company.…”
Section: Managerial Ownership and Performancementioning
confidence: 93%